A unique two-stage strength-ductility match in low solid-solution hardening Ni-Cr alloys: Decisive role of short range ordering. (15th March 2020) - Zhang, Y.J.; Han, D.; Li, X.W.
Abstract: The effect of short range ordering (SRO) on the strength-ductility match of low solid-solution hardening Ni-Cr alloys with high stacking fault energies (SFEs) were systematically investigated under tensile tests. With increasing Cr content, the SFE and friction stress keep almost unchanged but the SRO degree becomes enhanced; in this case, the deformation mechanism was evolved from wavy slip to planar slip, and deformation twinning was further induced as the Cr content exceeds 20 at.%, which leads to a unique two-stage strength-ductility match of Ni-Cr alloys. The action of SRO has merely played a decisive role for such an experimental phenomenon. Graphical abstract: Image, graphical abstract